Anaerobic degradation of anionic surfactants by indigenous microorganisms from sediments of a tropical polluted river in Brazil - Silveira Duarte, Iolanda Cristina (2015)
The aim of this study was to evaluate the ability of the microorganisms present in the sediment of the Tietê river to degrade anionic surfactant – linear alkylbenzene sulphonate (LAS)  in the reactor operated in batch sequences under denitrifying conditions.  The reactor was fed with synthetic substrate consisting of yeast extract, soluble starch, sodium bicarbonate and sucrose; LAS was added at different stages in concentration of 15 mg/l after 30 mg/L. Reduction in the concentration of co-substrates were evaluated in order to optimize the degradation of surfactant. The results showed that the efficiency of degradation of LAS is directly related to the population of denitrifying bacteria and that the Tietê River sediment can be used as inoculum for the treatment of LAS.  These bacteria were able to degrade LAS regardless of additional carbon source.  The removal of LAS and nitrate can be achieved simultaneously in wastewater with low organic load.